Culture, Health, and Religion at the Millennium: Sweden Unparadised - Demker, Marie; Leffler, Yvonne; Sigurdson, Ola (Palgrave Macmillan, 2020)
The book presents interpretations of culture, health, politics, and religion in Sweden today, Sweden transforms from the well-functioning but existentially bland economic wonder to a more fragmented and gloomy society. Contributors include scholars from film studies, literary studies, political science, religious studies and theology